Chapter The Creation of Two Ethnographic Identities: The Cases of the Ostrogoths and the Langobards - Kasperski, Robert (Reti Medievali E-Book, 2022)
The aim of this paper is to analyse two ethnographic identities constructed for two barbarian peoples - the Ostrogoths and the Langobards. As I try to argue, the first identity was constructed to show that the Ostrogoths were a civilized people and a better version of the Romans, and moreover, this identity communicated that the Ostrogoths could not be called a barbaric and savage people. Theoderic the Great's propagandists tried to present the Ostrogothic warriors as defenders of the Roman World. The second identity - constructed for the Langobards - presented them as a people who embodied the very antithesis of their main enemies c. 660: the Franks and the Romans. The origin of the Langobards and the genesis of their ethnic hallmark, i.e. the long beards, were presented as signs of distinction or limitic structures which communicated non-romanitas of this people.